DEMOGRAPHIC PROCESSES OF THE POPULATION IN THE SOUTHERN REGIONS OF THE BUKHARA EMIRATE (END OF THE 19th CENTURY - BEGINNING OF THE 20th CENTURY) (Eurasian Journal of History, Geography and Economics, 2024)
In this article, the issues of administrative procedure, social lifestyle, demographic situation of the population, national composition and ethnic composition of the population in the southern oases are scientifically analyzed. Also, information about the management system in the estates of this period is given.